Design, Analysis and Construction of an Impressed Current Electric Device for Cathodic Protection - Hammajam, A. A.; Ibrahim, M. A.; Adam, M. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This paper aimed at designing, analyzing and fabricating an impressed current electric device. Cathodic protection is a means to prevent corrosion by applying a flow of electrical current from an external source (anode) through the environment and to the metallic structure that is being protected. The protective current changes the environment around the metal thus halting the corrosion reaction. Cathodic protection is used to prevent corrosion in a wide range of applications where the structure being protected is surrounded by an environment that allows current flow. The impressed current cathodic protection systems have the benefit of using an external power supply to drive current. The study used sea water as electrolyte with locally constructed transformer rectifier and to select a proper material for the construction so as to illustrate the effect and how the impressed current system functions. The general performance evaluation was found that the device has a net driving potential of 10.5V and a life expectancy of 128 years of the anode. In conclusion, the construction was successful and easy to operate which can be used to protect metal structure against corrosion.